PENERAPAN METODE ROLE PLAYING PADA MATA PELAJARAN PPKN DI SEKOLAH DASAR - A Rahim; Rizky Dwiprabowo (Program Studi PGSD Universitas Flores, 2020)
The background of this research is the fact of the low learning outcomes of PPKn among SDN Jatimekar II Bekasi students, where most students have not reached the minimum completeness standard (KKM). The purpose of this study was to improve student PPKn learning outcomes in the Election and Pilkada Process material through the Role Playing Method in grade VI students in the odd semester of the 2018/2019 academic year. This research method is classroom action research (classroom action research). The model used is the model used is the Kurt Lewin Model with 2 cycles, where in each cycle there are four stages consisting of planning, acting, observing and reflecting. The research time was 4 months, from August to November 2018 with 20 students as research subjects, while data was collected through tests, interviews and observations. The results showed that there was a significant increase in PPKn learning outcomes on the Election and Pilkada Process material for grade VI students. This is evidenced by the results of the pre-cycle test 58.30 increased to 71.08 in cycle I, and in cycle II increased with an average value of 87.50. The results of this test are also supported by the results of interviews which show that PPKn learning on the Election and Pilkada Process material through the Role Playing Method can be fun, so that active learning is created.